Inclusion of leucaena leaf hay in the diet of laying hens during the growing phase - Alexsandro Nunes Oliveira; Ednardo Rodrigues Freitas; Carlos Eduardo Braga Cruz; Thales Marcel Bezerra Filgueira; Germano Augusto Jerônimo do Nascimento; Raffaella Castro Lima (Acta Scientiarum. Animal Sciences, 2014)
Current experiment evaluated the effects of inclusion of leucaena leaf hay (LLH) on the performance and nutrient digestibility of diets for laying hens during the growth phase (14-18 weeks). Ninety pullets (Rhode Island Red and New Hampshire) were distributed in a completely randomized design with three treatments (0%, 5% and 10% inclusion of LLH) and five replicates, with six birds. Feed intake (g bird-1 day-1), weight gain (g bird-1 day-1), feed conversion (kg kg-1), metabolizable energy intake (kcal bird-1 day-1), intake of crude protein (g bird-1 day-1), coefficients of dry matter (CDDM) and gross energy (CDCE), nitrogen digestibility (CDN), apparent metabolizable energy (AME) and apparent metabolizable energy corrected for nitrogen (AMEn) were evaluated. The inclusion of LLH did not statistically influence CDN, AME and AMEn of diet. However, this inclusion significantly affected CDDM and CDCE, resulting in lower CDDM and CDCE with inclusion of 10%. Whereas the use of nutrients by chicks fed on diets with the inclusion of LLH allowed the same amount of metabolizable energy, inclusion of up to 10% of LLH diet during the growth phase (14-19 weeks) of laying hens (Rhode Island Red and New Hampshire) may be recommended.